International Students in Indian UniversitiesVeena - Bhalla, Veena; Powar, Krishnapratap B. (International Higher Education, 2015)
In the new millennium the Indian higher education system has grown two and half times in terms of both the number of universities and the number of students. In comparison the growth in international students has been anaemic. The international students are largely from Asia and Africa. In 2012-13 40% of the students were female; 80% were studying at the under-graduate level, 18% at post-graduate level and 2% were in research. The liberal arts accounted for 30% and 70% were in professional streams, the maximum number being in medicine & health care (35%) followed by engineering & technology (23%) and management (9%).